Pseudocapacitance type positive electrode material and preparation method thereof, positive electrode plate and secondary battery
Preparing LiFeO2 positive electrode material by anodizing method solves the problem of insufficient charging and discharging rates and cycle life of existing secondary batteries, and achieves battery performance with high energy density, fast charging and discharging and long life.
Patent Information
- Application Number
- CN202411598528.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-04-11
AI Technical Summary
Existing secondary batteries face the problems of slow charging and discharge rates and short cycle life. The electronic conductivity of pseudocapacitor type electrode materials is insufficient, which limits their application in lithium-ion batteries.
The new pseudocapacitor type electrode material LiFeO2 was prepared by anodizing method. Through sintering and anodizing treatment, a positive electrode material with rich pore structure and active surface was generated.
The energy density and power density of the secondary battery are improved, the overall performance of the battery is enhanced, and the fast charging and discharging capacity and long cycle life are achieved.
Smart Images

Figure BDA0005128392430000101 
Figure BDA0005128392430000111 
Figure BDA0005128392430000121
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and specifically to a pseudocapacitive positive electrode material and a preparation method thereof, a positive electrode sheet and a secondary battery. Background Art
[0002] With the development of human society, people's demand for energy has also increased dramatically. Developing new energy sources, such as wind energy, solar energy, and tidal energy, is one of the important ways to solve energy shortages. However, these energy sources are intermittent and unevenly distributed, making their storage difficult. Electrochemical energy storage, as an efficient energy storage method, has been successfully applied in large-scale power grid energy storage, industrial and commercial energy storage, and household energy storage. Common electrochemical energy storage devices include secondary batteries and double-layer capacitors. Although secondary batteries have high energy density and long discharge time, they face the problems of slow charging and discharging rates and short cycle life; although double-layer capacitors have faster charging and discharging rates and a cycle life of up to 10,000 times, they also have the disadvantage of low energy density. Pseudocapacitor energy storage devices can fill the performance gaps of the two devices, while having good energy density, energy density, and cycle life. Among them, pseudocapacitor electrodes, as key components of the device, are crucial to its performance. Common pseudocapacitor electrode materials are mainly oxides, including RuO2, MnO2, and Nb2O5. Although RuO2 has high electronic conductivity, it is expensive; MnO2 and Nb2O5 have high theoretical specific capacity, but their low electronic conductivity limits their further application. Therefore, the development of new pseudocapacitive electrode materials plays an important role in secondary batteries, especially lithium-ion batteries. Summary of the invention
[0003] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, one purpose of the present application is a pseudocapacitive positive electrode material and a preparation method thereof, a positive electrode sheet, a secondary battery and an electrical device. The present application adopts an anodic oxidation method to prepare a new pseudocapacitive electrode material LiFeO2, which has the advantages of high electrochemical activity, simple synthetic raw materials, easy access, and low cost as a positive electrode material. In addition, the pseudocapacitive electrode material of the present application has a rich pore structure and active surface, which provides more storage space for ions, thereby accelerating the ion deintercalation rate, and has a strong ability to quickly charge and discharge, which effectively improves the energy density and power density of the secondary battery, thereby enhancing the overall performance of the secondary battery.
[0004] The first aspect of the present application provides a method for preparing a pseudocapacitive positive electrode material. According to an embodiment of the present application, the method comprises:
[0005] The iron source material, the lithium source material and the conductive agent are sintered to obtain a LiFeO2 precursor;
[0006] The LiFeO2 precursor is used as a working electrode, the working electrode and the counter electrode are placed in an electrolyte, anodized, and the precipitate is collected to obtain the pseudocapacitive positive electrode material.
[0007] According to the method of the embodiment of the present application, the present invention treats the sintered LiFeO2 precursor by anodization, so that it obtains electrons at the anode and is transformed into a positive electrode material with pseudocapacitive properties. In this process, the release of oxygen causes the material to expand, resulting in a rich pore structure and active surface. These newly added structural features provide more storage space for ions, thereby accelerating the rate of ion deintercalation, effectively improving the energy density and power density of the secondary battery, and thus enhancing the overall performance of the secondary battery.
[0008] According to an embodiment of the present application, the method for preparing a pseudocapacitive positive electrode material may also have the following additional technical features:
[0009] According to an embodiment of the present application, the molar ratio of the iron element in the iron source material to the lithium element in the lithium source material is (4.5-5.5):1.
[0010] According to an embodiment of the present application, based on the total mass of the iron source material, the lithium source material and the conductive agent, the total mass of the iron source material and the lithium source material accounts for more than 50% and less than 100%, and the mass of the conductive agent accounts for more than 0% and less than 50%.
[0011] According to an embodiment of the present application, the iron source material includes at least one of Fe2O3, FeOOH, Fe3O4 and FeC6H5O7 hydrate;
[0012] and / or, the lithium source material comprises at least one of LiOH·H2O, Li2O, Li2O2, Li2CO3 and LiC2O4;
[0013] And / or, the conductive agent includes at least one of graphite, acetylene black, Ketjen black, graphene, carbon nanotubes and carbon nanofibers.
[0014] According to an embodiment of the present application, before the sintering process, the iron source material, the lithium source material and the conductive agent are mixed and tableted to obtain an initial tablet.
[0015] According to an embodiment of the present application, the sintering process satisfies at least one of the following conditions:
[0016] The sintering temperature is 600℃~900℃, and the sintering time is 8h~72h;
[0017] The heating rate is 1℃ / min~10℃ / min;
[0018] Carry out under inert atmosphere protection.
[0019] According to an embodiment of the present application, the electrolyte includes a lithium salt and an organic solvent.
[0020] According to an embodiment of the present application, the charging voltage of the anodizing treatment is 3.8V to 4.4V, and the charging time is 4h to 48h.
[0021] According to an embodiment of the present application, the method further comprises:
[0022] The precipitate is washed, and the washed bottom precipitate is dried to obtain the pseudocapacitive positive electrode material.
[0023] According to an embodiment of the present application, the detergent used for washing includes at least one of nitrogen methyl pyrrolidone, anhydrous ethanol, dimethyl carbonate, diethyl carbonate, acetonitrile, dimethyl sulfoxide, and dimethylformamide;
[0024] And / or, the drying process is carried out under vacuum, wherein the vacuum degree is 1Pa-30Pa, the temperature is 70°C-100°C, and the time is 12h-48h.
[0025] The second aspect of the present application provides a pseudocapacitive positive electrode material. According to an embodiment of the present application, the pseudocapacitive positive electrode material is obtained by the method for preparing the pseudocapacitive positive electrode material according to the first aspect.
[0026] According to an embodiment of the present application, the specific surface area of the pseudocapacitive positive electrode material is 2 m 2 g -1 ~5m 2 g -1 .
[0027] The third aspect of the present application provides a positive electrode plate. According to an embodiment of the present application, the positive electrode plate includes the pseudocapacitive positive electrode material described in the second aspect.
[0028] The fourth aspect of the present application provides a secondary battery. According to an embodiment of the present application, the secondary battery includes the positive electrode sheet described in the third aspect.
[0029] The fifth aspect of the present application provides an electric device. According to an embodiment of the present application, the electric device includes the secondary battery described in the fourth aspect.
[0030] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0032] Figure 1 A flow chart of a method for preparing a pseudocapacitive positive electrode material according to an embodiment of the present application is shown;
[0033] Figure 2 The XRD pattern of the product prepared by the anodization method in Example 1 of the present application is shown;
[0034] Figure 3 The microscopic morphology of the electrode prepared by the anodizing method in Example 1 of the present application is shown as follows: (a) a scanning electron microscope photo of the electrode and (b) a local magnified image of the active material;
[0035] Figure 4 The cyclic voltammetry curves of the electrode prepared by the anodic oxidation method in Example 1 of the present application and the electrode prepared by the solid phase sintering method in the comparative example are shown;
[0036] Figure 5 The charge and discharge curves of the electrode prepared by the anodic oxidation method in Example 1 of the present application at different charge rates are shown;
[0037] Figure 6 The charge and discharge curves of the electrode prepared by the anodization method in Example 2 of the present application at different charge rates are shown. DETAILED DESCRIPTION
[0038] The embodiments of the present application are described in detail below. The embodiments described below are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application.
[0039] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of this application, unless otherwise specified, the meaning of "plurality" is two or more.
[0040] The endpoints and any values of the ranges disclosed in this application are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this application.
[0041] In the present application, the terms "comprise" or "include" are open expressions, that is, including the contents specified in the present application but not excluding other contents.
[0042] At present, in the prior art, LiFeO2 is mostly used as the negative electrode material of the battery, which is mainly prepared by solid phase sintering method. It has fewer electrochemical active sites and weaker ability of rapid charge and discharge. A few reports use anodic oxidation method to prepare iron-based hydroxide pseudocapacitor materials as negative electrode materials. Due to the presence of hydrogen, it is limited to aqueous system. The current lithium-ion batteries mainly use anhydrous organic electrolytes, so iron-based hydroxide pseudocapacitor materials are not applicable.
[0043] The present invention processes the sintered LiFeO2 precursor by anodization, so that it obtains electrons on the anode and is transformed into a positive electrode material with pseudocapacitive characteristics. In this process, the release of oxygen causes the material to expand, resulting in a rich pore structure and active surface. These newly added structural features provide more storage space for ions, thereby accelerating the ion deintercalation rate, and having a strong rapid charge and discharge capability, effectively improving the energy density and power density of the secondary battery, thereby enhancing the overall performance of the secondary battery.
[0044] To this end, the first aspect of the present application proposes a method for preparing a pseudocapacitive positive electrode material, see Figure 1 The method includes: S100 sintering treatment and S200 anodizing treatment. Each step will be described in detail below.
[0045] S100 sintering treatment
[0046] In this step, the iron source material, the lithium source material and the conductive agent are sintered to obtain a LiFeO2 precursor. During the sintering process, the iron source material and the lithium source material will undergo decomposition and recrystallization to form a precursor of lithium iron oxide (LiFeO2). Since the LiFeO2 precursor needs to be anodized later, a conductive agent is added during the early sintering process to improve the conductivity of the LiFeO2 precursor electrode.
[0047] According to an embodiment of the present application, the molar ratio of the iron element in the iron source material to the lithium element in the lithium source material is (4.5-5.5):1, for example, it can be 4.5:1, 4.6:1, 4.8:1, 5.0:1, 5.2:1, 5.4:1, 5.5:1. The molar ratio of lithium iron meets the above conditions, and the obtained pseudocapacitive positive electrode material has more transition metal active sites, which provides more storage space for ions, thereby accelerating the ion deintercalation rate and improving the energy density and power density of the secondary battery. In addition, the generation of inactive byproducts can be reduced.
[0048] According to an embodiment of the present application, based on the total mass of the iron source material, the lithium source material and the conductive agent, the total mass of the iron source material and the lithium source material accounts for more than 50% and less than 100%, and the mass of the conductive agent accounts for more than 0% and less than 50%. Exemplarily, the total mass of the iron source material and the lithium source material can account for 51%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 99%, and the mass of the conductive agent can account for 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 49%. Thus, in order to facilitate the lithium source material and the iron source material to fully react to generate a uniform LiFeO2 precursor, this precursor not only has a better crystal structure, but also exhibits good electrical conductivity, which provides favorable conditions for the subsequent anodic oxidation reaction, ensuring the thoroughness and uniformity of the oxidation process, thereby preparing a pseudocapacitive LiFeO2 material with excellent electrochemical properties. In addition, the generation of inactive by-products can be reduced.
[0049] According to an embodiment of the present application, the iron source material includes at least one of Fe2O3, FeOOH, Fe3O4 and FeC6H5O7 hydrate.
[0050] According to an embodiment of the present application, the lithium source material includes at least one of LiOH·H2O, Li2O, Li2O2, Li2CO3 and LiC2O4.
[0051] According to an embodiment of the present application, the conductive agent includes at least one of graphite, acetylene black, Ketjen black, graphene, carbon nanotubes and carbon nanofibers.
[0052] According to an embodiment of the present application, before the sintering process, the iron source material, the lithium source material and the conductive agent are mixed and sheeted to obtain an initial sheet. In some embodiments, the mixture of the iron source material, the lithium source material and the conductive agent is pressed to form a sheet structure, which is convenient for subsequent anodization as a working electrode.
[0053] According to an embodiment of the present application, the sintering process satisfies at least one of the following conditions:
[0054] The sintering temperature is 600°C to 900°C, for example, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, and the sintering time is 8h to 72h, for example, 8h, 12h, 18h, 24h, 30h, 36h, 42h, 48h, 54h, 60h, 66h, 72h;
[0055] The heating rate is 1°C / min to 10°C / min, for example, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min;
[0056] The reaction is carried out under an inert atmosphere, which includes argon or nitrogen.
[0057] If the sintering treatment meets the above conditions, a LiFeO2 precursor with a suitable structure can be obtained, which is beneficial to the subsequent anodization to generate a pseudocapacitive LiFeO2 positive electrode material.
[0058] S200 anodizing treatment
[0059] In this step, the LiFeO2 precursor is used as the working electrode, the working electrode and the counter electrode are placed in an electrolyte, anodized, and the precipitate is collected to obtain the pseudocapacitive positive electrode material. During the anodization process, the LiFeO2 precursor will obtain electrons at the anode and be transformed into a positive electrode material with pseudocapacitive properties. In this process, the release of oxygen causes the material to expand, resulting in a rich pore structure and active surface. These newly added structural features provide more storage space for ions, thereby accelerating the rate of ion deintercalation, strong rapid charge and discharge capabilities, and effectively improving the energy density and power density of the secondary battery, thereby enhancing the overall performance of the secondary battery. Exemplarily, the counter electrode includes a lithium sheet.
[0060] According to an embodiment of the present application, the electrolyte includes a lithium salt and an organic solvent. Exemplarily, the lithium salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium hexafluoroantimonate (LiAsF6), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium hexafluoroacetylacetonate (LiDFH), lithium bis(oxalate borate) (LiBOB), lithium bis(trifluoromethylsulfonyl imide) (LiTFSI), lithium difluorooxalate borate (LiDFOB), and lithium bis(difluorosulfonyl imide) (LiFSI); the organic solvent includes at least one of ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), propylene carbonate (PC), and 1,2-dimethoxyethane (DME).
[0061] According to an embodiment of the present application, the charging voltage of the anodizing treatment is 3.8V to 4.4V, for example, 3.8V, 3.9V, 4.0V, 4.1V, 4.2V, 4.3V, 4.4V; the charging time is 4h to 48h, for example, 4h, 12h, 18h, 24h, 30h, 36h, 42h, 48h. The charging voltage and time meet the above conditions, which can cause the LiFeO2 precursor to undergo an oxidation reaction to generate a LiFeO2 positive electrode material with pseudocapacitive properties, and accompanied by the release of oxygen, the material surface expands, resulting in a rich pore structure and active surface. These newly added structural features provide more storage space for ions, thereby accelerating the rate of ion deintercalation, effectively improving the energy density and power density of the secondary battery, and thus enhancing the overall performance of the secondary battery.
[0062] According to an embodiment of the present application, the method further comprises: washing the precipitate, and drying the washed bottom precipitate to obtain the pseudocapacitive positive electrode material. Thus, the residue on the surface of the LiFeO2 positive electrode material is removed by washing without affecting the physical and chemical properties of the LiFeO2 positive electrode material.
[0063] According to an embodiment of the present application, the detergent used for washing includes at least one of nitrogen methyl pyrrolidone, anhydrous ethanol, dimethyl carbonate, and diethyl carbonate. Exemplarily, the number of washings may be 1 time, 2 times, 3 times, 4 times, 5 times, 6 times, 7 times, 8 times, 9 times, and 10 times. Thus, the residue on the surface of the LiFeO2 positive electrode material is removed without affecting the physical and chemical properties of the LiFeO2 positive electrode material.
[0064] According to an embodiment of the present application, the drying process is carried out under a vacuum state, wherein the vacuum degree is 1Pa to 30Pa, for example, 1Pa, 2Pa, 5Pa, 10Pa, 15Pa, 20Pa, 25Pa, 30Pa, the temperature is 70°C to 100°C, for example, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, and the time is 12h to 48h, for example, 12h, 18h, 24h, 30h, 36h, 42h, 48h. Thus, the detergent on the surface of the LiFeO2 positive electrode material is removed, and the physical and chemical properties of the LiFeO2 positive electrode material are not affected.
[0065] The second aspect of the present application proposes a pseudocapacitive positive electrode material. According to an embodiment of the present application, the pseudocapacitive positive electrode material is obtained by the method for preparing a pseudocapacitive positive electrode material described in the first aspect. As a result, the pseudocapacitive positive electrode material of the present application has high electrochemical activity, rich pore structure and active surface, provides more storage space for ions, thereby accelerating the ion deintercalation rate, and has strong rapid charge and discharge capabilities, effectively improving the energy density and power density of the secondary battery, thereby enhancing the overall performance of the secondary battery.
[0066] According to an embodiment of the present application, the specific surface area of the pseudocapacitive positive electrode material is 2 m 2 g -1 ~5m 2 g -1 As a result, more storage space is provided for ions, thereby accelerating the rate of ion insertion and extraction, and having strong rapid charging and discharging capabilities, which effectively improves the energy density and power density of the secondary battery, thereby enhancing the overall performance of the secondary battery.
[0067] It should be noted that the features and advantages described above for the method for preparing the pseudocapacitive positive electrode material are also applicable to the pseudocapacitive positive electrode material and will not be described in detail here.
[0068] The third aspect of the present application proposes a positive electrode plate. According to an embodiment of the present application, the positive electrode plate includes the pseudocapacitive positive electrode material described in the second aspect. The positive electrode plate of the present application has high electrochemical activity, rich pore structure and active surface, provides more storage space for ions, thereby accelerating the ion insertion and extraction rate, and has strong rapid charging and discharging capabilities, effectively improving the energy density and power density of the secondary battery, thereby enhancing the overall performance of the secondary battery. The characteristics and advantages described above for the pseudocapacitive positive electrode material are also applicable to the positive electrode plate, and will not be repeated here.
[0069] According to an embodiment of the present application, the positive electrode active material layer may further include a conductive agent, for example, the conductive agent includes at least one of graphite, acetylene black, Ketjen black, graphene, carbon nanotubes and carbon nanofibers.
[0070] According to an embodiment of the present application, the positive electrode active material layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, and tetrafluoroethylene-hexafluoropropylene copolymer.
[0071] According to the embodiments of the present application, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet (such as positive electrode active material, conductive agent, binder) are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0072] According to an embodiment of the present application, the positive electrode plate further includes a positive electrode current collector, and the positive electrode active material layer is located on at least one side of the positive electrode current collector.
[0073] According to an embodiment of the present application, the positive electrode current collector may include a metal foil or a composite positive electrode current collector. For example, the metal foil may be aluminum foil. The composite positive electrode current collector may include a polymer material base and a metal layer formed on at least one side of the polymer material base. For example, the composite positive electrode current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT) and other substrates).
[0074] The fourth aspect of the present application proposes a secondary battery. According to an embodiment of the present application, the secondary battery includes the positive electrode sheet described in the third aspect. The secondary battery of the present application has good energy density and power density, strong rapid charge and discharge capability, and excellent overall performance. The features and advantages described above for the positive electrode sheet are also applicable to the secondary battery and will not be repeated here.
[0075] According to an embodiment of the present application, the secondary battery further includes a negative electrode sheet and a separator, wherein the separator is located between the positive electrode sheet and the negative electrode sheet. During the battery charging and discharging process, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0076] According to an embodiment of the present application, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one side surface of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material.
[0077] According to an embodiment of the present application, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), etc.).
[0078] According to an embodiment of the present application, the negative electrode active material may be a negative electrode active material for a battery known in the art. As an example, the negative electrode active material may include at least one of graphite, silicon carbon, and lithium titanate.
[0079] According to an embodiment of the present application, the negative electrode active material layer may further optionally include a binder. The binder may include at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0080] According to an embodiment of the present application, the negative electrode active material layer may further include a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, conductive agent olefins, and carbon nanofibers.
[0081] According to an embodiment of the present application, the negative electrode active material layer may optionally further include other auxiliary agents, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0082] According to an embodiment of the present application, a negative electrode sheet can be prepared in the following manner: the components for preparing a negative electrode sheet (such as a negative electrode active material, a conductive agent, a binder and any other components) are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on a negative electrode current collector, and after drying, cold pressing and other processes, a negative electrode sheet can be obtained.
[0083] The present invention has no particular limitation on the type of the isolation membrane, and any known porous structure isolation membrane with good chemical stability and mechanical stability can be selected. According to an embodiment of the present application, the isolation membrane may be made of at least one of glass fiber, non-woven fabric, polyethylene, polypropylene or polyvinylidene fluoride.
[0084] According to an embodiment of the present application, the secondary battery may include an outer package for packaging a positive electrode sheet, a negative electrode sheet, and an electrolyte.
[0085] According to an embodiment of the present application, the outer packaging may include a shell and a cover plate. The shell may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell has an opening connected to the receiving cavity, and the cover plate can be covered on the opening to close the receiving cavity.
[0086] According to an embodiment of the present application, the outer package of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell.
[0087] The outer packaging of the battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).
[0088] The secondary battery of the present application may include a battery cell form, a battery module form and a battery pack form. In some embodiments, the battery cells can be assembled into a battery module, and the number of battery cells contained in the battery module can be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery module. In some embodiments, the battery module can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery pack.
[0089] In the fifth aspect of the present application, an electric device is provided. According to an embodiment of the present application, the electric device includes the secondary battery described in the fourth aspect. As a result, the electric device of the present application has high-efficiency electrochemical performance. The features and advantages described above for the secondary battery are also applicable to the electric device and will not be repeated here.
[0090] Battery cells, battery modules, and battery packs can be used as power sources for electrical devices or as energy storage units for electrical devices. Electrical devices may include, but are not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships, satellites, energy storage systems, etc.
[0091] As an electrical device, a battery cell, battery module or battery pack can be selected according to its usage requirements.
[0092] As an embodiment, the electric device may be a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, etc. In order to meet the requirements of the electric device for high power and high energy density of the battery, a battery pack or a battery module may be used.
[0093] As another embodiment, the device may be a mobile phone, a tablet computer, a notebook computer, etc. The device is usually required to be light and thin, and a battery cell may be used as a power source.
[0094] The scheme of the present application will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the literature in this area or the product specification are carried out. The reagents used or the instruments that do not indicate the manufacturer are all conventional products that can be obtained commercially.
[0095] Example 1
[0096] This embodiment provides a method for preparing a novel pseudocapacitive positive electrode material, which specifically includes the following steps:
[0097] 1. Preparation of small original sheets: First, the iron source Fe2O3 and the lithium source LiOH·H2O are mixed according to the Fe:Li molar ratio of 5:1; then the iron source and lithium source mixture are mixed with graphite according to the mass ratio of m:n=70:30; finally, the mixed powder is punched into small original sheets under the action of a pressure of 10Mpa for sintering.
[0098] 2. Sintering: Heat the stamped small original piece to 850°C in an inert atmosphere of Ar gas at a heating rate of 5°C / min, react for 24 hours, and naturally cool to room temperature after the reaction is completed.
[0099] 3. Liquid phase anodization: The sintered small original piece is used as the working electrode and the lithium sheet is used as the counter electrode, and is placed in an electrolyte cell with an electrolyte of 1M LiPF6 (EC / PC / EMC=3:4:3), and then maintained at a voltage of 4.0V for 24h.
[0100] 4. Washing and purification: After anodization, the bottom precipitate was washed repeatedly 8 times with nitrogen methyl pyrrolidone (NMP), and then dried at 100°C in vacuum (vacuum degree of 20 Pa) for 24 h.
[0101] 5. Preparation of electrodes: The dried product is mixed with Super P and PVDF in a ratio of 8:1:1 to form a slurry, which is coated on aluminum foil and then punched into small original sheets with a certain diameter as LiFeO2 pseudocapacitive electrodes.
[0102] Electrochemical performance test: The prepared LiFeO2 pseudocapacitive electrode, lithium sheet, PP separator and electrolyte (LiPF6, EC / EMC=3:7) were assembled into a button cell, and then cyclic voltammetry test was performed.
[0103] The differences between Example 2 to Example 12 and Example 1 are shown in Table 1.
[0104] Table 1
[0105]
[0106] Comparative Example 1
[0107] This comparative example provides a method for preparing LiFeO2 material by solid phase sintering, which specifically comprises the following steps:
[0108] (1) Li2CO3 and Fe2O3 were weighed in a molar ratio of 1:1, and then ground in an agate mortar for 30 minutes to mix the two raw materials evenly, and then placed in a corundum crucible. The crucible containing the two raw materials was placed in a muffle furnace and heated at 600°C for 4 hours, then the heating was stopped, and the crucible was naturally cooled to room temperature. The crucible was taken out to obtain solid-phase sintered LiFeO2.
[0109] (5) Preparation of electrodes: The solid-phase sintered LiFeO2 was ground in an agate mortar for 30 min to refine the powder. The ground product was mixed with Super P and PVDF in a ratio of 8:1:1 to form a slurry, which was coated on aluminum foil and then punched into small original sheets with a certain diameter as a comparative example of the solid-phase sintered LiFeO2 electrode.
[0110] Electrochemical performance test: The prepared LiFeO2 electrode, lithium sheet, PP separator and electrolyte (LiPF6, EC / EMC=3:7) were assembled into a button cell, and then cyclic voltammetry test was performed.
[0111] Test Case
[0112] 1. X-ray diffraction analysis of the LiFeO2 cathode material powder prepared in Examples 1 to 12 shows that there are broad and gentle diffraction peaks in the range of diffraction angles of 20 to 30°, which is mainly related to the pores and active surfaces generated during the preparation process. This active surface stores defects and provides reaction sites for electrochemical reactions. The two diffraction peaks corresponding to angles of 33.52° and 43.76° are characteristic peaks of LiFeO2, indicating that the phase of the prepared material is LiFeO2. Taking Example 1 as an example, Figure 2 The X-ray diffraction pattern of the LiFeO2 positive electrode material powder prepared in Example 1 is shown.
[0113] When the cross-section of the LiFeO2 positive electrode prepared in Examples 1 to 12 is analyzed by scanning electron microscopy, it can be observed that there are a large number of micropores inside the particles, such as Figure 3 As shown (taking Example 1 as an example).
[0114] After the electrodes prepared in this application are assembled into button cells, the voltage at 2-3.5V vs. Li + / Li potential range, with a scan rate of 2 m V s -1 When the cyclic voltammetry (CV) scan is performed, a rectangular shape can be observed, and a pair of broad and large redox peaks are present at about 2.4 V vs. Li+ / Li (taking Example 1 as an example, Figure 4 The cyclic voltammetry scanning diagram is shown in Figure 1. These electrochemical characteristics indicate that the material of the present invention has the characteristics of pseudocapacitance.+ / Li has a pair of steep redox peaks. These characteristics indicate that the solid-phase sintered material does not have pseudocapacitive properties. In fact, it behaves as a battery. The differences in the potential range and electrochemical behavior of the two substances in Example 1 and Comparative Example 1 may be related to the different phases and surface properties obtained by different preparation methods.
[0115] 2. The specific surface area of the LiFeO2 positive electrode materials of Examples 1-12 and Comparative Example 1 was tested. The specific test steps are as follows:
[0116] The samples were first degassed at 200°C in vacuum for 2 h, and then subjected to a nitrogen isothermal (liquid nitrogen constant temperature) adsorption-desorption curve test to obtain specific surface area data.
[0117] The specific surface area test data show that the specific surface area of LiFeO2 obtained by solid phase sintering in Comparative Example 1 is 0.63 m 2 g -1 , and the specific surface areas of LiFeO2 obtained in Examples 1-12 are all higher than those in Comparative Example 1, which indicates that LiFeO2 prepared by the anode method can provide more active sites for electrochemical reactions.
[0118] Table 2
[0119]
[0120]
[0121] 3. The button cells assembled in Examples 1-12 were respectively subjected to charge and discharge tests at a charge and discharge rate of 0.1 to 10 C in a voltage range (2 to 3.5 V vs. Li+ / Li).
[0122] The battery charge and discharge performances of Examples 1-5 are similar. The charge and discharge test curves of Examples 1 and 2 are as follows: Figure 5 and Figure 6 For example, it can be seen that in the range of 0.1 to 1C, the charge and discharge curves are almost overlapped, and even in the high rate range of 5 to 10C, the characteristics of the charge and discharge curves do not undergo obvious deformation, indicating that the pseudocapacitor material prepared in the embodiment has fast charge and discharge performance.
[0123] Compared with Example 1, Example 6 has a relatively high lithium element and a relatively low iron element in the lithium source material and the iron source material, resulting in fewer transition metal active sites in the pseudocapacitive positive electrode material product, which leads to a low battery capacity.
[0124] Compared with Example 1, Example 7 has a low lithium element and a high iron element in the lithium source material and the iron source material, resulting in a pseudocapacitive positive electrode material product containing more inactive metal oxides, which leads to a low battery capacity.
[0125] In Example 8, compared with Example 1, the total mass of the lithium source material and the iron source material is relatively low, resulting in the pseudocapacitive positive electrode material product containing more inactive conductive agent, thereby causing the battery capacity to be low.
[0126] Compared with Example 1, the charging voltage of Example 9 is lower, resulting in that the anodic oxidation cannot be effectively carried out, and the product is mainly the precursor, resulting in low capacity of the battery.
[0127] Compared with Example 1, Example 10 has a higher charging voltage, which may cause the substances in the electrolyte to decompose and produce inactive decomposition products attached to the surface of the precipitate, thereby resulting in a low capacity of the battery.
[0128] Compared with Example 1, Example 11 has a shorter charging time, resulting in incomplete material etching, material waste, and a decrease in the capacity of the battery.
[0129] Compared with Example 1, Example 12 has a longer charging time. In the later stage of the reaction, more inactive precursors will be stripped off from the electrode and doped into the precipitate, resulting in a lower capacity of the battery.
[0130] Table 3
[0131]
[0132] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. A method for preparing a pseudocapacitive positive electrode material, characterized in that: include: The iron source material, the lithium source material and the conductive agent are sintered to obtain a LiFeO2 precursor; The LiFeO2 precursor is used as a working electrode, the working electrode and the counter electrode are placed in an electrolyte, anodized, and the precipitate is collected to obtain the pseudocapacitive positive electrode material.
2. The method according to claim 1, characterized in that The molar ratio of the iron element in the iron source material to the lithium element in the lithium source material is (4.5-5.5):
1.
3. The method according to claim 1, characterized in that Based on the total mass of the iron source material, the lithium source material and the conductive agent, the total mass of the iron source material and the lithium source material accounts for more than 50% and less than 100%, and the mass of the conductive agent accounts for more than 0% and less than 50%.
4. The method according to claim 1, characterized in that: The iron source material includes at least one of Fe2O3, FeOOH, Fe3O4 and FeC6H5O7 hydrate; and / or, the lithium source material comprises at least one of LiOH·H2O, Li2O, Li2O2, Li2CO3 and LiC2O4; And / or, the conductive agent includes at least one of graphite, acetylene black, Ketjen black, graphene, carbon nanotubes and carbon nanofibers.
5. The method according to claim 1, characterized in that Before the sintering process, the iron source material, the lithium source material and the conductive agent are mixed and tableted to obtain an initial tablet.
6. The method according to claim 1, characterized in that The sintering process satisfies at least one of the following conditions: The sintering temperature is 600℃~900℃, and the sintering time is 8h~72h; The heating rate is 1℃ / min~10℃ / min; Carry out under inert atmosphere protection.
7. The method according to claim 1, characterized in that The electrolyte includes a lithium salt and an organic solvent.
8. The method according to claim 1, characterized in that The charging voltage of the anodizing treatment is 3.8V to 4.4V, and the charging time is 4h to 48h.
9. The method according to claim 1, characterized in that: Further including: The precipitate is washed, and the washed bottom precipitate is dried to obtain the pseudocapacitive positive electrode material.
10. The method according to claim 9, characterized in that The washing agent used in the washing includes at least one of nitrogen methyl pyrrolidone, anhydrous ethanol, dimethyl carbonate, diethyl carbonate, acetonitrile, dimethyl sulfoxide, and dimethylformamide; And / or, the drying process is carried out under vacuum, wherein the vacuum degree is 1Pa-30Pa, the temperature is 70°C-100°C, and the time is 12h-48h.
11. A pseudocapacitive positive electrode material, characterized in that: The pseudocapacitive positive electrode material is obtained by the method for preparing a pseudocapacitive positive electrode material according to any one of claims 1 to 10.
12. The pseudocapacitive positive electrode material according to claim 11, characterized in that: The specific surface area of the pseudocapacitive positive electrode material is 2 m 2 g -1 ~5m 2 g -1 .
13. A positive electrode sheet, characterized in that: It comprises: a positive electrode active material layer, wherein the positive electrode active material layer comprises the pseudocapacitive positive electrode material according to claim 11 or 12.
14. A secondary battery, characterized in that: Including the positive electrode sheet as described in claim 13.
15. An electrical equipment, characterized in that: Includes the secondary battery as claimed in claim 14.